IMPACT OF THE COVID-19 PANDEMIC ON HOUSEHOLD INCOME - Mirzamakhmudova, Madina Odiljon Kizi (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The social protection program will help reduce poverty in the country, improve the living conditions of socially vulnerable groups, and strengthen their income base. The effectiveness of the social protection programs implemented in the country is reflected in the results achieved as a result of their implementation. The article examines the program for the protection of socially vulnerable groups of the population in the Republic of Uzbekistan, poverty and the impact of the Covid-19 pandemic on the income of the population.